The price of the current civilisation - Sachs, J.D.; Musa, G.; Moghavvemi, S. (2013)
This paper is an extract from the public lecture delivered by Professor Dr. Jeffrey D. Sachs, at the invitation of Genting Berhad, in the Lim Goh Tong Lecture Hall of the Faculty of Business and Accountancy, University of Malaya. The lecture was the second in its series delivered on 23 October 2012.